Across state lines: Fulminant Babesia microti infection in a liver transplant recipient. Issue 5 (31st July 2017) - Meissner, Eric G.; McGillicuddy, John W.; Squires, Jerry; Skipper, Daniel; Self, Sally; Wray, Dannah; Moritz, Erin D.; Stramer, Susan L.; Nadig, Satish
Abstract: The potential for transmission of Babesia microti by blood transfusion is well recognized. Physicians may be unaware that products used for transfusion may be collected from geographically diverse regions. We describe a liver transplant recipient in South Carolina who likely acquired B. microti infection from a unit of blood collected in Minnesota.